Enhancing visual literacy of students through photo elicitation. Issue 1 (3rd April 2019) - Chai, Choon-Lee
Abstract: In this photo elicitation assignment, each student must take, select, and interpret a picture about a social issue that he/she has learned about in class. The student must then craft either a sensory poem, or answer the SHOWeD questions as designed by Shaffer and modified by Wang, which facilitates the student's interpretation of the picture. As a teaching tool, photo elicitation offers a range of pedagogical values; it enables visualization of students' everyday experiences, elicits personal meaning and emotion, promotes real-life and active learning, engenders critical consciousness, and enhances the visual literacy of students in terms of their visual "writing" and "thinking" skills.